2018
DOI: 10.1002/anie.201801818
|View full text |Cite
|
Sign up to set email alerts
|

Facile Stabilization of the Sodium Metal Anode with Additives: Unexpected Key Role of Sodium Polysulfide and Adverse Effect of Sodium Nitrate

Abstract: Sodium metal is an attractive anode for next-generation energy storage systems owing to its high specific capacity, low cost, and high abundance. Nevertheless, uncontrolled Na dendrite growth caused by the formation of unstable solid electrolyte interphase (SEI) leads to poor cycling performance and severe safety concerns. Sodium polysulfide (Na S ) alone is revealed to serve as a positive additive or pre-passivation agent in ether electrolyte to improve the long-term stability and reversibility of the Na anod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
134
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 180 publications
(136 citation statements)
references
References 34 publications
1
134
1
Order By: Relevance
“…Na 2 S 6 alone was found to improvet he electrochemical performance of the sodium-metal anode, even at ac urrent density as high as 10 mA cm À2 and ac apacity of 5mAh cm À2 over 100 cycles. [72] Unexpectedly,i nc ontrast to Li 2 S 6 ÀLiNO 3 ,w hich wasr eported to enhance the performance of the LiÀSb attery through as ynergistic effect, Na 2 S 6 ÀNaNO 3 was found to be detrimental on sodium metal. In an attempt to explain the startling effect, XPS analysisr evealed that the predominant SEI layer buildingm aterials,i fN a 2 S 6 alone was used, were of inorganic nature,e nlisting Na 2 O, Na 2 S 2 ,a nd Na 2 S. This, in turn, provided am echanicallys table SEI layer capable of suppressing sodium dendrite growth.…”
Section: Additives For Metal Nbrbsmentioning
confidence: 99%
See 1 more Smart Citation
“…Na 2 S 6 alone was found to improvet he electrochemical performance of the sodium-metal anode, even at ac urrent density as high as 10 mA cm À2 and ac apacity of 5mAh cm À2 over 100 cycles. [72] Unexpectedly,i nc ontrast to Li 2 S 6 ÀLiNO 3 ,w hich wasr eported to enhance the performance of the LiÀSb attery through as ynergistic effect, Na 2 S 6 ÀNaNO 3 was found to be detrimental on sodium metal. In an attempt to explain the startling effect, XPS analysisr evealed that the predominant SEI layer buildingm aterials,i fN a 2 S 6 alone was used, were of inorganic nature,e nlisting Na 2 O, Na 2 S 2 ,a nd Na 2 S. This, in turn, provided am echanicallys table SEI layer capable of suppressing sodium dendrite growth.…”
Section: Additives For Metal Nbrbsmentioning
confidence: 99%
“…Inspired by the analogues use of Li 2 S n −LiNO 3 in the Li−S battery, Li and co‐workers evaluated sodium polysulfide (Na 2 S 6 ) alone and as a coadditive with sodium nitrate (NaNO 3 ) in ether‐based electrolyte. Na 2 S 6 alone was found to improve the electrochemical performance of the sodium‐metal anode, even at a current density as high as 10 mA cm −2 and a capacity of 5 mAh cm −2 over 100 cycles . Unexpectedly, in contrast to Li 2 S 6 −LiNO 3 , which was reported to enhance the performance of the Li−S battery through a synergistic effect, Na 2 S 6 −NaNO 3 was found to be detrimental on sodium metal.…”
Section: Additives For Metal Nbrbsmentioning
confidence: 99%
“…Na 2 S 6 was found to boost the electrochemical performance of the Na electrode for over 100 cycles at high current density (10 mA cm −2 ) and cycled capacity (5 mAh cm −2 ). [ 290 ] However, while the combination of Li 2 S 6 and LiNO 3 is reported to enhance the performance of Li–S battery via a synergistic effect, the use of only Na 2 S 6 is preferred with Na. In fact, XPS analysis revealed that the SEI layer contains Na 2 O, Na 2 S 2 , and Na 2 O, which provide a mechanically stable SEI capable of suppressing (reducing) Na dendrite growth when only Na 2 S 6 is present ( Figure 18 a).…”
Section: Electrode/electrolyte Interphases In Sodium Batteriesmentioning
confidence: 99%
“…Similarly with lithium metal anode, Na metal batteries using conventional organic liquid electrolyte are facing some challenges, such as dendrite growth, volume changes, solid electrolyte interphase (SEI), suggesting an inferior cyclability and poor safety . Numerous efforts have been made to deal with abovementioned issues and obtain great achievements on the protection of sodium metal, such as artificial SEI, electrolyte additive, superconcentrated electrolyte, membrane modification, and 3D current collectors . Still, the inherent serious safety issues of the volatile and flammable of organic liquid electrolyte are like a sword hanging on the air.…”
mentioning
confidence: 99%